Pengaruh Bioscreen Anti Radiasi dari Tanaman Sansevieria trifasciata lorentii mein liebling terhadap Penurunan Radiasi Laptop - Novia Ardhya Maryana; Choirul Amri; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2018)
Advances in science and technology encourage people to develop and create various types ofelectronic devices. One of electronic equipments that is used widely in present day is laptop.Laptop as a product of modern technology still bring impact to our lives, one of which is radiation. The effect of radiation released by laptops is not directly perceived by the users, but after15-20 years. Sansevieria is one of plants that can be used as anti radiation bioscreen. The purpose of this study was to determine the decrease differences of laptop radiation before andafter being given anti radiation bioscreen made from Sansevieria trifasciata lorentii mein liebling. This research method was experiment with pre test post test with control group design.The data were analyzed descriptively and inferentially. The results reveal that the radiation incontrol group decreased in average of 0,32 x ???? (18,22 %), while in the treatment group, itwas 0,33 x ????(24,45 %).